An application of Marquardt's procedure to the seismic inverse problem - Keys, R.G. (Proceedings of the IEEE, 1986)
The seismic inverse problem is to infer characteristics of the subsurface from measurements of the wave field at the surface. The Marquardt procedure offers one approach to this problem. In applying this procedure, a linear relationship is developed between the wave field and some parameter which describes a physical property of the subsurface. Then a selection criterion is designed to choose the subsurface parameter which provides the best match for the observed seismic data.